Multibeam bathymetry raw data (Kongsberg EM 122 working area dataset) of RV MARIA S. MERIAN during cruise MSM112/2 - Gavin D extquotesingleMello; Gustavo Binda Souza; Frank Nitsche (PANGAEA, 2023)
The multibeam echo sounder (MBES) data was collected from the 24.11.2022 (02:52 UTC) to the 03.12.2022 (22:52 UTC) with a Kongsberg EM122 during the transit from Cartagena (Colombia) to Las Palmas (Canary Islands, Spain) in the Atlantic Ocean. The deep-water MBES EM122 operates with an acoustic frequency of 12 kHz and a beam opening angle of 2° x 2°. The system was used in the dual-swath mode with up to 864 beams per ping. The raw and unprocessed bathymetric and backscatter data is stored in Kongsberg format (*.all), each containing up to 30 min of data. The therein included time, motion and position data (WGS84, geographic) was measured by the Kongsberg Seapath system on board. During the acquisition the echo sounder was monitored as well as settings and filter adjusted according to the environment. The swath opening angle was set between 65° and 70°. As the data was collected during transit, no specific survey was performed. Sound velocity profiles (SVP) were measured on the 23.11., 25.11., 29.11., and 30.11.22 with a CTD and applied in the MBES acquisition software SIS to ensure high quality measurement. The SVP data is not part of this submission but can be extracted from the *.all files.